(untitled) (Olhares, 2019)
This research’s proposal is centered in the investigation of the possibilities and potentialities that Augusto Boal’s Image Theater method has when applied to a collective of university students. During the encounters, Image Theater’s exercises were used and provided the participants the chance to question and reflect about their opinions and points of view about the themes chosen to be discussed during these meetings and relate them to the physical actions created during the execution of these exercises. The results allow us to conclude that the Image Theater promoted reflections and deepen perceptions about nowadays subjects and made possible a wider dialogue between the members of a group of university students about the chosen subjects.